2011
DOI: 10.5137/1019-5149.jtn.4201-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive estimation of cerebral perfusion pressure with transcranial Doppler ultrasonography in traumatic brain injury

Abstract: AIM:In traumatic brain injury (TBI) patients, to overcome the secondary insults, cerebral perfusion pressure (CPP) oriented therapy is recommended. The study is assigned to estimate CPP values with middle cerebral artery (MCA) flow velocities measured noninvasively using transcranial Doppler ultrasonography (TCD). MATeRIAL and MeTHods:Forty-seven TBI patients were studied. Intracranial pressure (ICP), mean arterial pressure (MAP) and MCA flow velocities of the patients were monitored. Invasive CPP was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Third, we used non-invasive measurements to estimate ICP. While several studies have shown correlation between CBFV as measured by TCD and ICP it is possible that invasive monitoring would reveal more significant changes [21,27,28]. Fourth, a single provider performed all palpations.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we used non-invasive measurements to estimate ICP. While several studies have shown correlation between CBFV as measured by TCD and ICP it is possible that invasive monitoring would reveal more significant changes [21,27,28]. Fourth, a single provider performed all palpations.…”
Section: Discussionmentioning
confidence: 99%
“…Gura et al used this formula to estimate CPP with a correlation coefficient of 0.92 (p < 0.0001). 7 An estimation difference of 10 mm Hg for CPP is an accept able tradeoff between the risk of an indwelling catheter and the benefit of a noninvasive method to estimate CPP.…”
Section: Discussionmentioning
confidence: 99%
“…concluded that Independent of the type of intracranial pathology, there is a strong correlation between PI intranscranial Doppler ultrasonography (TCD) and invasive ICP measurements. [ 35 ] Also Ragauskas et al . showed that Doppler ultrasound of OA is precise and accurate compared with gold standard CSF pressure measured via lumbar puncture.…”
Section: Discussionmentioning
confidence: 99%